2020
DOI: 10.1111/phen.12321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on the development and fecundity of Microplitis similis (Hymenoptera: Braconidae), a parasitoid of Spodoptera litura (Lepidoptera: Noctuidae)

Abstract: Microplitis similis (Hymenoptera: Braconidae) is a solitary endoparasitoid of Spodoptera litura larvae (Lepidoptera: Noctuidae). Here, the effects of constant temperature (18, 21, 24, 27, 30, 33 and 36 °C) on the development and fecundity of M. similis developing in S. litura were studied in the laboratory to clarify the range of its potential distribution and better understand its potential as a biological control agent. The developmental duration of M. similis varied from 10.6 (33 °C) to 27.9 days (18 °C). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The results showed that, when the temperature in the growth chamber was raised from 27 °C to 36 °C, the pupal developmental duration of A. bambawalei was significantly shortened from 7.05 to 5.63 days, and the fecundity and growth rate increased by 40%. The above results are consistent with those of Yi et al [ 30 ]; that is, at higher temperatures, rapid ovarian maturation and acceleration of egg and embryonic development of insects were observed. These results indicate that high temperatures may be conducive to A. bambawalei [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that, when the temperature in the growth chamber was raised from 27 °C to 36 °C, the pupal developmental duration of A. bambawalei was significantly shortened from 7.05 to 5.63 days, and the fecundity and growth rate increased by 40%. The above results are consistent with those of Yi et al [ 30 ]; that is, at higher temperatures, rapid ovarian maturation and acceleration of egg and embryonic development of insects were observed. These results indicate that high temperatures may be conducive to A. bambawalei [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…The larvae of S. litura are hosts for the parasitoid wasp M. similis, which is an important biological control agent of the herbivore. M. similis can reduce the weight gain and feed intake of the S. litura larvae and can increase larval mortality [26,27]. In addition, M. similis is a vector of insect ascoviruses-vesicle virus.…”
Section: Introductionmentioning
confidence: 99%
“…A life table is an essential research method for dissecting the impact of environmental factors on insect population dynamics (Chi & Getz, 1988;Chi & Su, 2006;Tuan et al, 2016). The life table parameters have been widely used to evaluate the development and reproduction of pests (Qiu et al, 2012;Yi et al, 2020). The net reproductive rate, generation time, gross reproductive rate and fecundity of T. flavus were the highest at 19 C (Table 2).…”
Section: Discussionmentioning
confidence: 99%